Research on MTRF Deployment Scheme of 4G Mobile Network - Zhigang Xie; Weihua Bao (Dianxin kexue)
The LTE provides voice services for users by CSFB technology. The MTRF function can solve the problems that unsuccessful circuit switched fallback on the edge of CSFB. The deployment of MTRF function involves the range of network remake. By analyzed the problem of unsuccessful circuit switched fallback on the edge of CSFB and studied the principle of MTRF, two deployment proposal were provided. They could be used in different scales of networks. The results could be provided a reference for the follow -up network construction.